Офицерский крематорий - Нестеров Михаил Петрович (Спецназ ГРУ, 2015)
Экземпляры: ф-20 (20210611) / Инвентарный номер: 57128 / Цена: 50.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Н 56 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6